Energy absorption in lattice structures in dynamics: Nonlinear FE simulations. (April 2017) - Ozdemir, Zuhal; Tyas, Andrew; Goodall, Russell; Askes, Harm
Highlights: A numerical analysis framework has been developed that captures the experimentally observed dynamic response of micro-lattices. The framework has been demonstrated to be accurate and robust across two lattice geometries and two loading rates, with responses monitored at both the impact face and the distal face of the sample. The results suggest that simple MDoF models can be developed to capture the response of such geometries under fast loading regimes. Abstract: An experimental study of the stress–strain behaviour of titanium alloy (Ti6Al4V) lattice structures across a range of loading rates has been reported in a previous paper [1]. The present work develops simple numerical models of re-entrant and diamond lattice structures, for the first time, to accurately reproduce quasi-static and Hopkinson Pressure Bar (HPB) test results presented in the previous paper. Following the development of lattice models using implicit and explicit non-linear finite element (FE) codes, the numerical models are first validated against the experimental results and then utilised to explore further the phenomena associated with impact, the failure modes and strain-rate sensitivity of these materials. We have found that experimental results can be captured with good accuracy by using relatively simple numerical models with beam elements. Numerical HPB simulations demonstrate that intrinsic strain rate dependence of Ti6Al4V is not sufficient to explain the emergent rate dependence of the re-entrant cube samples. There is also evidence that, whilst re-entrant cube specimens made up of multiple layers of unit cells are load rate sensitive, the mechanical properties of individual lattice structure cell layers are relatively insensitive to load rate. These results imply that a rate-independent load-deflection model of the unit cell layers could be used in a simple multi degree of freedom (MDoF) model to represent the impact behaviour of a multi-layer specimen and capture the microscopic rate dependence.